Understanding of Wood Anomalies in Metallic Gratings From Phase Gradient Metasurfaces - Quan, Jiaqi; Zhou, Qingjia; Cao, Yanyan; Xu, Yadong (Frontiers in Materials, 2022)
Phase-gradient metasurfaces (PGMs) have provided unprecedented opportunities for manipulating light. Here, we reexamine ordinary and well-studied subwavelength metallic gratings (OMGs) from the concept of PGMs to provide more insight into their diffraction properties. We will show that due to the existence of gauge invariance in PGMs, i.e., the diffraction law of PGMs is independent of the choice of initial value of abrupt phase shift that induces the phase gradient, the well-studied OMGs can be regarded as a PGM strictly, with its diffraction properties can be fully predicted by generalized diffraction law with phase gradient. In particular, the generalized diffraction law reveals that the phase gradient plays a significant role in the famous effect of Wood’s anomalies and Rayleigh’s conjecture.